Perlindungan Hukum Bank atas Hak Tanggungan dalam Pembatalan Sertipikat Tanah (RechtJiva, 2025)
This journal discusses legal protection for creditors, especially banks, against the cancellation of certificates of ownership of land that is being burdened with Underwriting Rights. Mortgage rights are a guarantee that provides creditors of legal certainty for the receivables given to the debtor. However, in practice, problems often occur where land certificates that have been used as guarantees of cancellation due to administrative disabilities or ownership disputes, giving rise to legal uncertainty for creditors. This study uses the research method, namely juridical normative statutory approach (statute approach) and comparative study. Analysis of relevant laws and regulations, such as the Mortgage Act (Law No. 4 of 1996), as well as court decisions relating to the cancellation of land certificates. This research also examines legal certainty and creditor protection in the land system in Indonesia. The results showed that although the Mortgage Rights provide legal protection for creditors, the cancellation of land certificates still has the risk of loss of creditors for the guarantee that has been given. Based on Article 18 of the Mortgage Rights Law, the Underwriting Rights will fall if the land rights they burdened are also deleted. Therefore, legal efforts are needed for creditors to maintain their rights, both through a civil lawsuit mechanism, confiscation of guarantees (conservatoir beslag), as well as the execution of auction on debtor assets. To reduce the risk of cancellation of certificates, this study recommends strengthening regulations regarding creditors' protection, increasing the accuracy of land administration by the National Land Agency (BPN), as well as the application of digital -based land registration systems to increase transparency and prevent future land disputes.